Pelesapan subjek dalam lagu denny caknan: Kajian pragmasintaksis - Khoironi, Haris; Mahbub, Moh. Tarojjil; Zihan, Ahmad Khawarizmy; Sawardi, FX (Universitas Lampung, 2025)
This study aims to analyze the pattern of subject ellipsis in the clauses of Denny Caknan’s song lyrics. Ellipsis is a linguistic phenomenon in which a word or linguistic unit is not explicitly mentioned, but its meaning can be understood from the context. Using a qualitative descriptive method, this research collects data through the listening method and note-taking technique, which are then analyzed using techniques such as direct element division, inversion, ellipsis, and substitution. The findings indicate that subject ellipsis in these lyrics results in a more concise and effective narrative, although it requires contextual understanding from the listener. The listener’s understanding of subject ellipsis is highly dependent on the context of the preceding lyrics and their ability to fill in the missing syntactic elements, making them an active part of the interpretation process. These findings are expected to enrich linguistic studies on ellipsis and contribute to further research on subject ellipsis.Keywords: ellipsis, syntax, pragmatics, song lyrics, Denny Caknan